Kulturelle Alterität als Exilerfahrung - Sabina Becker (Recherches Germaniques)
Döblin’s American exile is both ambivalent and contradictory: on the one hand, he acknowledged early on that the USA was little more than a “country of asylum in exile” (‘Asylland im Exil’). On the other hand, he approached American culture and way of life with curiosity and openness, and he concluded his Californian years with unreserved approval and a declaration of love. Döblin’s explicitly intercultural positioning as a representative of literary modernism and urbanism should be analyzed in relation to the biographical dimension of his exile and leads to the consideration of whether and how intercultural writing in exile can be linked with the experience of alterity in a foreign environment. Based on autobiographical testimonies and memoirs, the article sheds light on Döblin’s encounters with America as well as on his paradigmatic role as an eminent representative of literary modernism and urbanism.